KEHADIRAN NEGARA TERHADAP ANAK PADA PERKAWINAN TIDAK TERCATAT DI KABUPATEN BOVEN DIGOEL - PAPUA - Karepesina, Abdullah (Prodi Hukum Keluarga Islam IAI Uluwiyah Mojokerto, 2026)
This study examines the presence of the state in guaranteeing and protecting the rights of children born from unregistered marriages in Boven Digoel Regency, Papua. Unregistered marriages have a direct impact on population administration and give rise to various legal problems that seriously affect the fulfillment of children’s rights. This research employs a qualitative approach using field research methods (case study), with data collected through interviews, observations, and documentation. Data analysis is conducted descriptively and analytically by applying relevant legal theories and concepts of child protection. The findings indicate that children of parents without a marriage certificate experience various administrative legal problems, including difficulties in obtaining birth certificates, limited access to public services, weak fulfillment of inheritance and property rights, as well as inadequate legal and social protection. These conditions place children in a vulnerable position, both juridically and socially. Nevertheless, further findings show that the state is present through various policies and legal mechanisms to provide solutions to these problems, such as the issuance of birth certificates, recognition and determination of a child’s lineage, and the provision of access to public services and social protection. The presence of the state reflects a concrete effort to guarantee children’s civil and population rights and affirms the state’s commitment to protecting children as legal subjects, even when their parents’ marriage is not administratively registered.